Potensi Senyawa Aktif Mengkudu (Morinda citrifolia) sebagai Antifungi Candida albicans melalui Pendekatan in Silico - Khaerunissa Anbar Istiadi; Erma Suryanti; Dewi Chusniasih (Wahana-Bio: Jurnal Biologi dan Pembelajarannya, 2023)
Candida albicans is a normal microbiota in humans. However, the imbalance and increasing number of C. albicans can cause infections in the vagina, mouth, esophagus, and nails. Sap-3 plays role in the infections especially in the adhesion process, and can used as a therapeutic target for C.albicans. Here an attempt has been made to analyze the potential of the active compounds from noni (Morinda citrifolia) as an antifungal by molecular docking towards Sap-3 protein. Drug-likeness characteristics were analyzed based on the Lipinski Rule of Five. Validation of molecular docking of Sap-3 protein-native ligand was conducted followed by molecular docking of the Sap3 protein-test based on the Lamarckian Genetics Algorithm. The highest binding energy is Beta-sitosterol (-8.77 kcal/mol), followed by Alizarin (-6.47 kcal/mol), Morindone (-6.51 kcal/mol), Quercetin (-5.76 kcal/mol), Pepstatin A (-5.55 kcal/mol), Scopoletin (-5.26 kcal/mol), Kaempferol (-5.13 kcal/mol). Bioactive compounds from noni (Morinda citrifolia) can be an appropriate choice as antifungal and for further experiments through in vitro and in vivo tests.